Identification of TRDV-TRAJ V domains in human and mouse T-cell receptor repertoires - Volkmar, Michael; Fakhr, Elham; Zens, Stefan; Bury, Alice; Offringa, Rienk; Gordon, Jessica; Huduti, Enes; Wölfel, Thomas; Wölfel, Catherine (Frontiers in Immunology, 2023)
Here, we describe the identification of two T-cell receptors (TRs) containing TRDV genes in their TRA chains, the first one in human and the second one in mouse. First, using 5’RACE on a mixed lymphocyte-tumor cell culture (MLTC), we identified TRDV1 5’-untranslated region (UTR) and complete coding sequence rearranged productively to TRAJ24. Single-cell TR RNA sequencing (RNA-seq) of the MLTC, conducted to identify additional clonotypes, revealed that the analysis software detected the hybrid TRDV-TRAJ TRA (TRA) chain but excluded it from the final results. In a separate project, we performed TR sequencing of tumor-infiltrating lymphocytes (TILs) in a murine tumor model. Here, the predominant clonotype contained a TRA chain with a TRDV2-2-TRAJ49 rearrangement. Again, the hybrid TRA chain was not reported in the final results. Transfection of both TR cDNAs resulted in cell surface localization of TR together with CD3, suggesting a productive protein in both cases. Tumor recognition of the Homo sapiens (Homsap) TRDV1-containing TR could be demonstrated by IFN Gamma ELISA ELISpot kit, whereas the Mus musculus (Musmus) TR did not recognize a tumor-derived cell line. To determine whether the TRDV-containing TRA chains we detected were rare events or whether TRDV genes are commonly incorporated into TRA chains, we queried the NCBI Sequence Read Archive for TR single-cell RNA-seq data and analyzed 21 human and 23 murine datasets. We found that especially Homsap TRDV1, Musmus TRDV1, and to some extent Musmus TRDV2-2 are more commonly incorporated into TRA chains than several TRAV genes, making those TRDV genes a relevant contribution to TRA diversity. TRDV-containing TRA chains are currently excluded from the final results of V-(D)-J dataset analyses with the CellRanger software. We provide a work-around to avoid exclusion of those hybrid TRA chains from the final analysis results.